Walking away: the disengagement and de-radicalization of a violent right-wing extremist. (4th May 2017) - Horgan, John; Altier, Mary Beth; Shortland, Neil; Taylor, Max
ABSTRACT: This article presents a case study of one individual's trajectory through violent right-wing extremism in the USA. Drawing on an in-depth in-person interview conducted with 'Sarah', we trace the influences affecting the nature and extent of her involvement, engagement and disengagement. We focus on delineating the complexity of Sarah's disengagement from violent extremism. Her account supports several claims in the literature. First, there is rarely any single cause associated with individual disengagement. Rather, the phenomenon is a dynamic process shaped by a multitude of interacting push/pull factors, sunk costs and the perceived availability of alternatives outside the group. Second, as this case illustrates, prison affords physical separation from the violent extremist group and with it, time to reflect which may be critical to sustaining disengagement. Third, this account illustrates how de-radicalization may be a long-term process, and may in some cases supersede rather than precede one's exit, even where disillusionment precedes disengagement. Finally, Sarah's case suggests the successful adoption of a new social role and sense of identity as a potentially important protective factor in reducing the risk of re-engagement.